Utilization of Palm Oil Fuel Ash and Eggshell Powder as Partial Cement Replacement - A Review - Wan Inn Goh; Noridah Mohamad; Muhammad Tahir Lakhiar; Ashfaque Ahmed Jhatial; Samiullah Sohu (Salehan Institute of Higher Education, 2018)
The increase in population leads to increase in construction of houses and other buildings to accommodate these people. The extensive use of concrete for constructional purposes leads to release of Carbon Dioxide (CO2) gas into the atmosphere which adds to the already increased global warming. The increase in urbanization has also lead to increased generation of waste materials. These waste materials are by-products, which are disposed in landfills causing environmental and health issues. The utilization of agricultural wastes as cement substitute is a great alternative for reducing the use and production of cement, which contributes to 5% to 7% of global CO2 emissions alone. Palm Oil Fuel Ash (POFA) Eggshells are two major agricultural wastes, which are generated in abundance in Malaysia. This paper reviews the combined utilization of Eggshells Powder (ESP) and POFA as potential partial cement replacement material and development of bio-concrete, which may help in reducing the environmental issues that are caused by the agricultural by-products. They have been used successfully but individually in concrete. The pozzolanic activity triggered by POFA requires Calcium Hydroxide which cement provides to a limit. Eggshells when grinded into Eggshells Powder (ESP) are rich in calcium oxide and can provide the required calcium hydride and enhance the pozzolanic reaction.